Jesus the village psychiatrist: A summary - Donald Capps (HTS Teologiese Studies/Theological Studies, 2010)
This paper was a response to a panel discussion on the author’s book, Jesus the village psychiatrist, published by Westminster John Knox Press, Louisville, KY, 2008 which formed part of the Society of Biblical Literature’s Psychology and Biblical Studies Section, 21–24 November 2009, New Orleans, LA. The response consisted of an explanation of somatoform disorders, a summary of the book and the following case studies: the case of Fraulein Elisabeth, the case of paralytics, the case of blind persons, the demon-possessed boy, the case of the woman with a haemorrhage, the healings of lepers and the woman who cared for Jesus. The paper concluded with a discussion on words and their power to cure. It illustrated how symptomatology had changed from paralysis in the 19th century to chronic fatigue in the first half of the 20th century to stress today.